PENGEMBANGAN LEMBAR KERJA SISWA DENGAN PENDEKATAN SAINTIFIK PADA PELAJARAN BAHASA INGGRIS DI KELAS IV SD NEGERI 101775 SAMPALI - Eva Betty Simanjuntak; Mifta Khairina (JURNAL HANDAYANI PGSD FIP UNIMED, 2018)
Abstract : Development of Student Worksheets in Scientific Approach inEnglish Language Lessons in Class IV of the Public Elementary School 101775Sampali. This study aims to improve student learning outcomes in English subjects.The results of this study are that the validation of student worksheets is relativelygood, this can be seen from the assessment carried out by the validator. The resultsobtained from the design expert validation obtained an average score of 3.53, thevalidation of the material experts obtained an average score of 3.93, while the expertvalidation of the education practitioners obtained an average score of 4.00. Thus, itcan be concluded that student worksheets (LKS) with a scientific approachdeveloped by researchers are worthy of being used as teaching materials to supportlearning in grade IV of elementary school.Keywords : Research and Development, Van den Akker Model, Scientific ApproachAbstrak : Pengembangan Lembar Kerja Siswa Pada Pendekatan Saintifik PadaPelajaran Bahasa Inggris di Kelas IV SD Negeri 101775 Sampali. Penelitian inibertujuan untuk meningkatkan hasil belajar siswa pada mata pelajaranbahasa Inggris. Hasil penelitian ini adalah validasi lembar kerja siswa tergolongbaik, hal ini dapat dilihat dari penlaian yang dilakukan oleh validator. Hasil yangdiperoleh dari validasi ahli desain memperoleh skor rata- rata 3,53, validasi dari ahlimateri memperoleh skor rata-rata 3,93, sedangkan validasi ahli praktisi pendidikanmemperoleh skor rata-rata 4,00. Dengan demikian, maka dapat disimpulkanbahwa lembar kerja siswa (LKS) dengan pendekatan saintifik yangdikembangkan oleh peneliti layak digunakan sebagai bahan ajar untukmendukung pembelajaran kelas IV Sekolah Dasar.Kata kunci : Researchand Development, Model Van den Akker, PendekatanSaintifik